Clinical efficacy of cytoreductive surgery and hyperthermic chemotherapy in peritoneal carcinomatosis from gastric cancer. Issue 10 (October 2011) - Ströhlein, Michael A; Bulian, Dirk R; Heiss, Markus M
Evaluation of: Yang XJ, Huang CQ, Suo T et al. Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy improves survival of patients with peritoneal carcinomatosis from gastric cancer: final results of a Phase III randomized clinical trial. Ann. Surg. Oncol. 18(6), 1575–15781 (2011). Peritoneal carcinomatosis (PC) is the most common pattern of metastasis and recurrence in patients with gastric cancer and is associated with poor clinical outcome and survival. Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) was recently established as a new treatment option for PC of gastrointestinal cancer. However, the role of cytoreductive surgery in gastric cancer and the intrinsic role of HIPEC remains unclear. The evaluated article presented a single center Phase III study, randomizing 68 patients with PC from gastric cancer to surgical cytoreduction only (CRS; n = 34) versus cytoreduction plus HIPEC with cisplatin and mitomycin (CRS+HIPEC; n = 34). Median overall was 6.5 months in the CRS group and 11.0 months in the CRS+HIPEC group (p = 0.046). Serious adverse events were acceptable in both groups. Multivariate analysis found CRS+HIPEC, synchronous PC, complete cytoreduction, systemic chemotherapy >6 cycles and no incidence of severe adverse events independent predictive factors for survival. This was the first study to show the positive effects of HIPEC in addition to CRS in PC independently of the tumor entity. In patients with gastric cancer, multimodal treatment concepts combining surgical cytoreduction and HIPEC may provide a new option in carefully selected patients.